2005
DOI: 10.1381/096089205774512447
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colorectal Surgery in Obese Patients

Abstract: With sufficient experience, laparoscopic colorectal surgery in obese patients is feasible and safe. It is associated with no increased risk of complications and preserves all benefits of the mini-invasive approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 5 publications
0
50
1
Order By: Relevance
“…Studies in Western populations have shown that obese patients undergoing laparoscopic colorectal surgery are at increased risk of conversion to an open procedure [1][2][3]17]. It is unclear, however, whether complication rates are higher and operative times are longer in obese patients who undergo laparoscopic resection [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Western populations have shown that obese patients undergoing laparoscopic colorectal surgery are at increased risk of conversion to an open procedure [1][2][3]17]. It is unclear, however, whether complication rates are higher and operative times are longer in obese patients who undergo laparoscopic resection [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions With sufficient experience, laparoscopic colorectal surgery in obese Asian patients is feasible and safe, offering all the benefits of a minimally invasive approach. Management of Asian colorectal cancer patients with BMI C 30 kg/m 2 requires meticulous perioperative care, and colorectal surgeons must be familiar with obesityrelated challenges in such patients.Keywords Colorectal cancer Á Laparoscopic surgery Á Body mass index Á Asian Á Obesity Although obesity is associated with various health risks and is considered a risk factor for postoperative morbidity after abdominal surgery, the effect of obesity on the outcomes of laparoscopic colorectal surgery is unclear [1][2][3][4][5][6][7][8]. In the past, obesity was considered to be a relative contraindication to laparoscopy, as the condition was associated with technical difficulties during the procedure [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also have used variable definitions of morbid obesity. Most studies [10][11][12][13] have compared outcomes for obese (BMI [ 30 kg/m 3 ), and nonobese (BMI \ 30 kg/m 3 ) patients undergoing LC, with comparable reported outcomes. Conversely, other studies [3,14] have reported significantly greater postoperative morbidity BMI body mass index a A P value less than 0.05 is considered statistically significant b Wilcoxon rank sum test for obese than for nonobese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that SSI increases with obesity, one reason being a decrease in blood circulation in fat tissues. [8][9] Recent preliminary findings from a study of patients who underwent coronary artery bypass graft showed a significant relationship between increasing levels of HbA1c and SSI rates. Also, increased glucose levels (>200 mg/dL) in the immediate postoperative period (<48 hours) were associated with increased SSI risk.…”
Section: Age and Sex Distributionmentioning
confidence: 99%